2020
DOI: 10.1590/1983-21252020v33n310rc
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Defense Mechanisms in Tomato Plants by Saprobic Fungi Filtrates Against Early Blight Disease

Abstract: Tomato plants can be attacked by several diseases. The early blight disease causes large losses to tomato growers and requires many applications of fungicide for its control. Thus, the objective of this work was to evaluate the effect of saprobic fungi filtrates on the control of early blight (Alternaria solani) in tomato plants. The treatments consisted of fungi filtrates (Stachylidium bicolor - SBI; Periconia hispidula - PHI; Brachysporiella pulchra - BPU; Myrothecium leucotrichum - MLE; and Pycnoporus sangu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…P. sanguineus extract was already used to control Pseudocercospora griseola (Viecelli et al 2010) and Xanthomonas axonopodis pv. phaseoli (Toillier et al 2010) in bean, and Xanthomonas vesicatoria (Assi et al 2017) and Alternaria solani (Alencar et al 2020) in tomato. Our research group showed the effectiveness of crude extract of P. sanguineus basidiocarps to control M. javanica in tomato (Barbosa et al 2021), but without the characterization of potential bioactive compounds.…”
Section: P Sanguineus Is a Saprophytic Fungus Belonging To Division B...mentioning
confidence: 99%
“…P. sanguineus extract was already used to control Pseudocercospora griseola (Viecelli et al 2010) and Xanthomonas axonopodis pv. phaseoli (Toillier et al 2010) in bean, and Xanthomonas vesicatoria (Assi et al 2017) and Alternaria solani (Alencar et al 2020) in tomato. Our research group showed the effectiveness of crude extract of P. sanguineus basidiocarps to control M. javanica in tomato (Barbosa et al 2021), but without the characterization of potential bioactive compounds.…”
Section: P Sanguineus Is a Saprophytic Fungus Belonging To Division B...mentioning
confidence: 99%
“…Given the above, an overview of the scientific work carried out with endophytic fungi to induce resistance can be seen in Table 2. [190] Neotyphodium lolii Lolium perenne Alternaria alternata, Curvularia lunata and Fusarium avenaceum [191] Fusarium solani sensu lato S. lycopersicum Fusarium oxysporum f. sp. radicis-lycopersici, Septoria lycopersici [192] Trichoderma harzianum S. lycopersicum Alternaria solani, Phytophthora infestans, Botrytis cinerea [193,194] T. harzianum, T. asperellum, T. atroviride, T. strigosum and T. longibrachiatum Cucumis sativus Colletotrichum lagenarium [195] T. virens S.lycopersicum Fusarium oxysporum f. sp.…”
Section: Endophytes In Induced Resistancementioning
confidence: 99%
“…Resistance induction uses biotic and abiotic inducers as an alternative control method, in order to activate the defense mechanisms of plants (ALENCAR et al, 2020). The use of plant resistance inducers has been reported in tropical flowers to reduce the incidence of diseases that compromise quality (GURGEL et al, 2018), reducing the useful life.…”
Section: Introductionmentioning
confidence: 99%